(untitled) (University Arena, 2025)
Background. The idea of free time has worried people since ancient times. Aristotle once said “that free time does not mean the end of work, but, on the contrary, work means the end of free time.” It should be used for recreational activities, creation, literature, science, art, philosophy and sports. Today, the concept of leisure time acquires a richer understanding, apart from time for rest, recreation, fun-leisure, tourism, time for training and professional development, to improve one’s methods, all this after he has fulfilled his professional, family and social obligations. Aspirations and behaviour related to (regarding) free time and the way of using space in this leisure time, have changed profoundly in recent years in Romania as well. The researchers, know that practicing physical activity regularly, leads to substantial and lasting benefits in terms of health and quality of life. Objectives. The purpose of this study consists in understanding the place that sports activities occupy in the life regime of the UB students. Methods. Research methods: scientific documentation, questionnaire-based on investigation, statistical- mathematical processing and graphical interpretation. The survey was conducted in 2019 and consisted of a questionnaire, containing a set of 8 questions applied to a number of 100 students of the University of Bucharest. Results. Following the multiple answers regarding the proportion of sports activities in the students’ life regime, the subjects have opted as it follows: 76% do occasional sports, and only 16%, systematically. Unfortunately, 8% do not play sports at all. Most students (90%) prefer recreational sports and only 2% do performance sports and 8% do not play sports at all. Regarding the type of sports activities preferred by students, on the first place in overall standings were those for relaxation and leisure, with a percentage of 44%, followed by those for body maintenance, with 42%, the third place is occupied by races and contests, with 6% and 8% do not play sports at all. Among the sports activities practiced by the students during the weekend we specify fitness, jogging, soccer and swimming. Conclusion. Free time has a special impact on the life of each human being. This can be an advantage or a disadvantage, depending on how it is used. The study revealed that the students use a part of their free time for socializing and sedentary activities, but also for practicing sports.